Valley Polarization: A Single Chiral Nanoparticle Induced Valley Polarization Enhancement (Small 37/2020). Issue 37 (17th September 2020) - Kim, Sejeong; Lim, Yae‐Chan; Kim, Ryeong Myeong; Fröch, Johannes E.; Tran, Thinh N.; Nam, Ki Tae; Aharonovich, Igor
Abstract : In article number 2003005, Sejeong Kim, Ki Tae Nam, and co‐workers achieve a large degree of circular polarization (≈45%) at room temperature using a single chiral plasmonic nanoparticle on a transition metal dichalcogenide (TMD) monolayer. The chiral nanoparticle also induces circularly‐polarized luminescence with a linear excitation, which has been rarely reported.